TRANSLATION PROCEDURES IN PATIENT INFORMATION LEAFLETS - Rahmawati Rahmawati; Busmin Gurning; Sri Minda Murni (Universitas Negeri Medan, 2019)
The aims of this study were to find out the types of translation procedures in Patient Information Leaflets, to describe the realization of translation procedures and to explain about the reason of certain translation procedures realized in Patient Information Leaflets.The research was conducted by using qualitative descriptive design. The data of this study was translation unit that consists of words, phrases, clauses and sentences in Patient Information Leaflets in two versions, English as the source text and Bahasa Indonesia as the target text. The data was analyzed by using the theory of Translation Procedures based on (Vinay and Darbelnet ; 2000) to find the types, realization and the reason of certain translation procedures were used in Patient Information Leaflets. The results of the study were (1) there were eight types of translation procedures in patient information leflets namely borrowing, calque, literal translation, transposition, modulation, equivalent, deletion and mixing procedures. (2)There were some realization of translation procedures in patient information leaflets , namely pure loanwords, naturalization, word for word translation, optional transposition, obligatory transposition, free modulation, obligatory modulation, equivalency, reduction, and combining procedures, and (3) there were seven reasons behind the realization of translation procedures namely the concept of the source text is unknown, preserving the verbatim meaning of the source text, unequivalent grammatical structures between source language and target language, naturalism in translation, clarity in translation, familiarity and maintaining the original terms of the source text.Key Words: Translation, Translation Procedures, Patient Information Leaflets, English and Bahasa Indonesia.